Effect of hydraulic retention time on chemical oxygen demand and total nitrogen removal in intermittently aerated constructed wetlands - Da Silva, Isabela Pires [UNESP]; Da Costa, Gabriela Barbosa [UNESP]; Queluz, João Gabriel Thomaz [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2020)
This study evaluated the effect of hydraulic retention time on chemical oxygen demand (COD) and total nitrogen (TN) removal in an intermittently aerated constructed wetlands. Two horizontal subsurface-flow constructed wetlands were used: One without aeration and the other aerated intermittently (1 hour with aeration/7 hours without aeration). Both systems were evaluated treating domestic wastewater produced synthetically. The flow rate into the two CWs was 8.6 L day-1 having a hydraulic retention time of 3 days. The results show that the intermittently aerated constructed wetland were highly efficient in removing COD (98.25%), TN (83.60%) and total phosphorus (78.10%), while the non-aerated constructed wetland showed lower efficiencies in the removal of COD (93.89%), TN (48.60%) and total phosphorus (58.66). These results indicate, therefore, that intermittent aeration allows the simultaneous occurrence of nitrification and denitrification processes, improving the removal of TN in horizontal subsurface-flow constructed wetlands. In addition, the use of intermittent aeration also improves the performance of constructed wetlands in removing COD and total phosphorus.
Remoção de DQO e Nitrogênio Total em alagados construídos com aeração intermitente em relação ao tempo de detenção hidráulica
Keywords: Ecotechnology; Effluent treatment; Nutrients removal